Bebida funcional a base de Solanum sessiliflorum (cocona) endulzado con Stevia rebaudiana (estevia) - Panduro Bendezú, Patricia Alexandra (2022)
The lacking of functional drinks of Amazonian fruits with health benefits was the reason for the elaboration of a functional drink based on Solanum sessiliflorum (cocona) with Stevia revaudiana (stevia) with the appropriate technological parameters and its respective file was proposed technique. The research was of a quantitative approach, of an experimental type, to carry out the project a totally randomized design was applied. Nine treatments were formulated, for which 3 equal volumes of cocona pulp of 500 ml each were made, 3 different amounts of water (500ml, 750ml, 1lt), and 3 different amounts of stevia (0.01%, 0.025%, 0.045%). The final formulation of the functional drink was sample C3 (dilution 1:1 with 0.045% stevia), with thermal treatment of 75 ° C by 5, presenting physicochemical values of acidity 1.18%, pH 3.81 and 3.27 ° Brix, nutritional minutes of proteins (0.46%), carbohydrates total (3.53%), total fiber (2.91%), Vitamin C (2.74 mg / 100g) and energy (20.41 Kcal). The results of the microbiological analyzes are within the range established by the NTS N ° 071-MINSA / DIGESA - V.01. 2008. The antioxidant activity of the functional drink determined by the DPPH method presented a value of 1.84 μg of Trolox /ml of sample. Has a shelf life of 4 months and 1 day, thanks to the preservative used, which was 0.05% potassium sorbate.